Hubungan Lingkungan Sosial Terhadap Kepatuhan Masyarakat Menerapkan Physical Distancing di Masa Pandemi Covid-19 - Stephanie Dwi Guna; Mesye Tanrozi; Deswinda Deswinda; M Zul'Irfan (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
The COVID-19 pandemic has become a dilemma as the spread of virus is rapid and difficult to be controlled. Physical distancing is one of the actions to prevent the virus transmission by reducing the contact between people. In contemplation of the pandemic management can become success, peple need to comply with the physical distancing act. This researh aimed to determine the relationship between social environment and physical distancing compliance of community during the COVID-19 pandemic. This research was correlation study with cross sectional approach. This study involved 154 respondents in Pekanbaru and used simple random sampling technique. The data related to the social environment and physical distancing compliance of community was being taken by using questionnaire which was proved valid and reliable. The result of this research showed that 63% respondent had positive social environment and 53.9% respondent complied to physical distancing during the COVID-19 pandemic. It was also determined that social environment was related to the physical distancing compliance of community during the COVID-19 pandemic (p=0.01 and OR=2.397). Social environment was related to the physical distancing compliance of community during the COVID-19 pandemic